2015
DOI: 10.1620/tjem.236.155
|View full text |Cite
|
Sign up to set email alerts
|

Salvia Miltiorrhiza Bge.f.alba Ameliorates the Progression of Monocrotaline-Induced Pulmonary Hypertension by Protecting Endothelial Injury in Rats

Abstract: Pulmonary hypertension (PH) is a life-threatening disease that is characterized by elevated pulmonary blood pressure, abnormally thickened pulmonary arteries, and right ventricular hypertrophy. Monocrotaline (MCT) has been used to generate an experimental model of PH in rats, with PH initiated from injuries of lung vascular endothelium. Salvia Miltiorrhiza Bge.f.alba is a widely used traditional herb in China, known to exert protective effects on vascular endothelial cell injury in animal experiments. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Salvia miltiorrhiza injection (SMI), a Chinese Materia Medica standardized product extracted from the root of red-rooted Salviae Miltiorrhizae ( Salvia miltiorrhiza Bunge, Labiatae, Danshen in Chinese), is an injectable solution through modern formulation and preparation process. The main ingredient is tanshinone, which plays an active role in the treatment of many diseases such as promoting blood circulation, removing blood stasis, reducing inflammatory reaction, and improving coagulation, as well as other effects [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salvia miltiorrhiza injection (SMI), a Chinese Materia Medica standardized product extracted from the root of red-rooted Salviae Miltiorrhizae ( Salvia miltiorrhiza Bunge, Labiatae, Danshen in Chinese), is an injectable solution through modern formulation and preparation process. The main ingredient is tanshinone, which plays an active role in the treatment of many diseases such as promoting blood circulation, removing blood stasis, reducing inflammatory reaction, and improving coagulation, as well as other effects [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Salvia miltiorrhiza Bge. ( Wang Y. et al, 2015 ), Crataegus oxyacantha ( Ahmadipour et al, 2017 ), Mimosa pigra ( Rakotomalala et al, 2013 ), Panax notoginseng ( Zhao et al, 2015 ), and Allium macrostemon Bunge ( Han et al, 2017 ) increased NO production.…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%
“…In addition, the regulation of Ca 2+ is one of the effects of Salvia miltiorrhiza Bge. on PAH ( Wang Y. et al, 2015 ) . Moreover, Panax notoginseng reduces the expression of p38MAPK that has been demonstrated to be an underlying mechanism in the generation of PAH ( Zhao et al, 2015 ).…”
Section: Preclinical Studies Of Traditional Herbal Medicine For Pulmonary Arterial Hypertension Treatmentmentioning
confidence: 99%